A green and facile method for the preparation of a pH-responsive alginate nanogel for subcellular delivery of doxorubicin. Issue 90 (1st October 2015) - Xue, Yanan; Xia, Xiaoyang; Yu, Bo; Luo, Xiaogang; Cai, Ning; Long, Sihui; Yu, Faquan
<x xml:space="preserve">Abstract</x> A one-pot preparation of a drug-loaded alginate nanogel was achieved upon the optimization of the concentration and their ratio of alginate, calcium ion and doxorubicin. The nanogel exhibited apparent pH-responsive release and subcellular delivery.